Structural characterization of two endopolysaccharides from Phellinus sp. and their immunologic effects by intragastric administration in a healthy mammalian model. Issue 2 (31st January 2018) - Ma, Xiao-kui; Ma, Yao; Peterson, Eric Charles; Guo, Wen ying; Li, Zhong Yu; Li, Yu
Abstract : Two purified endopolysaccharides derived from Phellinus sp. can improve the immune response by increasing the production of cytokines in the healthy mice. Abstract : Two purified endopolysaccharides derived from cultured Phellinus sp., individually named SHIP-1 and 2, were structurally characterized, along with an evaluation of their in vivo influential immunomodulatory activity in a healthy mammalian model. The structure of SHIP-1 was mainly composed of →4)-α-d -Fucp-(1→, →3, 6)-α-d -Araf-(1→ and →2, 4)-β-d -Galp-(→, with four residuals of α-d -Manp-(1→ and one α-d -Glcp-(1→ as sidegroups, while the planar structure and the heteronuclear multiple-bond correlation of SHIP-2 were not able to be analyzed. Biochemical analysis in the healthy mice model demonstrated that SHIP-1 increased the concentrations of the detected cytokines in a dosage-dependent manner but not in a time-dependent way. SHIP-2 exerted a positive effect in a dose-dependent manner over time for interferon gamma (IFN-γ) and interleukin (IL)-2 cytokine production at elevated dosages of 200, or 350 mg kg −1 d −1, while IFN-alpha(α) and IL-4 production was observed only in a dosage-dependent manner even at high dosages. Thus, SHIP-1 and 2 significantly improved the immune response through the intragastric administration of the tested high dosages by increasing the production of cytokines in the healthy mice, and these polysaccharides could possibly be used as an immunopotentiator in health foods or dietary supplements.